2015
DOI: 10.4269/ajtmh.15-0383
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Study of Interepidemic Rift Valley Fever Virus Infection Among Persons with Intense Ruminant Exposure in Madagascar and Kenya

Abstract: In this cross-sectional seroepidemiological study we sought to examine the evidence for circulation of Rift Valley fever virus (RVFV) among herders in Madagascar and Kenya. From July 2010 to June 2012, we enrolled 459 herders and 98 controls (without ruminant exposures) and studied their sera (immunoglobulin G [IgG] and IgM through enzyme-linked immunosorbent assay [ELISA] and plaque reduction neutralization test [PRNT] assays) for evidence of previous RVFV infection. Overall, 59 (12.9%) of 459 herders and 7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
2
13
2
1
Order By: Relevance
“…At first glance, the variation of RVF FOIs estimated from mid-1992 to mid-2014 is in accordance with the historical report of RVF transmission in Madagascar: high transmission during the 2008–09 outbreaks and low transmission outside this period12161718192021. Then, our results are consistent with the hypothesis of contrasted patterns of long-term RVFV enzootic circulation in the different Malagasy eco-regions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…At first glance, the variation of RVF FOIs estimated from mid-1992 to mid-2014 is in accordance with the historical report of RVF transmission in Madagascar: high transmission during the 2008–09 outbreaks and low transmission outside this period12161718192021. Then, our results are consistent with the hypothesis of contrasted patterns of long-term RVFV enzootic circulation in the different Malagasy eco-regions.…”
Section: Discussionsupporting
confidence: 91%
“…The central Highlands are characterized, during the dry season, by a cold environment unfavorable for RVF vectors132930. Yet, recurrent RVFV circulation has been detected in cattle in mid-2009, 2010–2011 and in human in 2012 in this region171819. Finally, our estimations showed an unexpected FOI peak in mid-2002/mid-2003 in the northwestern and the Highlands regions.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We showed that the RVFV IgG prevalence for all three counties investigated was 36.4%. This is in the higher range compared to previous studies from Northeastern Kenya [43][44][45], and 15-25% in 2009-2012 [1,23,46,47]. Our findings showed males were at a significantly higher risk of infection by RVFV than females, and increased age was associated with higher RVF IgG prevalence.…”
Section: Discussioncontrasting
confidence: 60%
“…Despite a recurrent circulation of RVFV (Andriamandimby et al, 2010;Ratovonjato et al, 2011;Gray et al, 2015) and the abundance of potential vectors (Tantely et al, 2015), no study on vector competence has been carried out in Madagascar to date. To better understand the mechanisms behind the maintenance and transmission of RVFV in Madagascar, the present study was designed to evaluate the vector competence of Cx.…”
mentioning
confidence: 99%